SB 796: a high-velocity RRc star. Issue 4 (22nd October 2018) - Gomel, Roy; Shahaf, Sahar; Mazeh, Tsevi; Faigler, Simchon; Crause, Lisa A; Sefako, Ramotholo; Segransan, Damien; Maxted, Pierre F L; Soszyński, Igor
ABSTRACT: We report here on a detailed study of a c-type RR Lyrae variable (RRc variable), SB 796, serendipitously discovered in a search of the WASP public data for stars that display large photometric periodic modulation. SB 796 displays a period of P = 0.26585 d and semi-amplitude of ∼0.1 mag. Comparison of the modulation shape and period with the detailed analysis of Large Magellanic Cloud variables indicates that SB 796 is an RRc variable. Gaia DR2 classification corroborated our result. Radial-velocity (RV) follow-up observations revealed a periodic variation consistent with a sine modulation, with a semi-amplitude of 5.6 ± 0.2 km s −1, and a minimum at phase of maximum brightness. Similar amplitude and phase were previously seen in other RRc variables. The stellar averaged RV is ∼250 km s −1, turning SB 796 to be a high-velocity star, while its present position, as derived from the Gaia astrometry, is at ∼3.5 kpc below the Galactic plane. Integration of the stellar Galactic motion shows that SB 796 oscillates at a range of 0.5–20 kpc Galacto-centric distance, passing near the Galactic centre about three times in 1 Gyr. The Galactic radial motion takes SB 796 up and down the plane to a scale height of ∼10 kpc. During its ∼10 Gyr estimated lifetime, SB 796 therefore passed ∼30 times near the Galactic centre.